Public Choice - Kurrild-Klitgaard, Peter; Shughart II, William F.; Leeson, Peter T.; Kaminski, Marek; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Public Choice deals with the intersection between economics and political science. The journal was founded at a time when economists and political scientists became interested in the application of essentially economic methods to problems normally dealt with by political scientists. It has always retained strong traces of economic methodology, but new and fruitful techniques have been developed which are not recognizable by economists. Public Choice therefore remains central in its chosen role of introducing the two groups to each other, and allowing them to explain themselves through the medium of its pages. Officially cited as: Public Choice.
Keywords: Political science; Public finance; Public Finance; Political Science